The Impact of Climate Change on Forest Ecosystems: A Biomolecular Perspective - Chai, Nong; Pong, Ming; Kiat, Ton (Research of Scientia Naturalis, 2024)
Climate change has emerged as one of the most significant environmental challenges of our time, profoundly affecting forest ecosystems worldwide. Recent studies have revealed that alterations in temperature, precipitation patterns, and atmospheric CO2 concentrations are causing unprecedented changes at the molecular level within forest organisms. Understanding these biomolecular responses is crucial for predicting and managing forest ecosystem resilience in the face of climate change. This study aimed to investigate the molecular mechanisms underlying forest species' adaptation to climate change and identify key biomarkers associated with stress response and resilience. The research employed a comprehensive approach combining transcriptomics, proteomics, and metabolomics analyses of various forest species across different climatic zones. Samples were collected from 20 forest sites over a three-year period, analyzing molecular responses to temperature fluctuations, drought stress, and elevated CO2 levels. Results demonstrated significant alterations in gene expression patterns related to heat shock proteins, antioxidant enzymes, and stress-responsive transcription factors. Notable changes were observed in metabolic pathways involved in carbon fixation, water use efficiency, and secondary metabolite production. The study identified 15 novel molecular markers associated with climate resilience in forest species. Furthermore, findings revealed distinct biomolecular adaptation strategies among different species and ecological niches. This research concludes that understanding molecular responses to climate change is essential for developing effective forest conservation strategies and predicting ecosystem adaptability. The identified molecular markers can serve as valuable tools for monitoring forest health and implementing targeted conservation measures in the face of ongoing climate change.